Sustainable Supply Chain Management and Optimization (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue is dedicated to the investigation and optimization of supply chain management in the context of sustainable development. In order to meet the needs of social development, enterprises are gradually innovating their supply chains to achieve sustainable development. Sustainable supply chain management can improve the competitiveness of enterprises; promote the sustainable development of enterprises; and realize the coordinated development of society, the economy, and the environment. However, the current development of sustainable supply chain management is not perfect. Therefore, scholars have become more and more interested in investigating supply chain management optimization. Supply chain management problems usually include product production and pricing, transportation location, upstream and downstream supply, and marketing problems. Existing research usually selects some of these problems and combines optimization methods, such as data-driven robust optimization methods, to optimize the status quo. Finally, an optimized scheme can be obtained, and some constructive suggestions are put forward to achieve sustainable and optimized development of supply chain management.